A comparative case study of Sony Computer Entertainment's crisis communication efforts during two PlayStation Network crises - Ahlstén, Jaakko (2015)
This study is about the crisis communication efforts of Sony Computer Entertainment (SCE) during two crises. Their PlayStation Network online service was hacked in 2011 and crashed by artificially high traffic in 2014. The purpose of the study is to examine the communication strategies of SCE and the development those strategies underwent between the two crises. This is done by comparing their crisis communication strategies with the Contingency Theory of strategic conflict management. This is done by a comparative case study methodology, utilising content analysis and gauging the impact of the crisis communication efforts through select media reactions. The study is significant in that it examines a severe data theft from a major international company, the like of which are more than likely to happen in the future. This study can be used as reference to build best practices for crisis communication strategies in crises involving online services and private data. The study results also support Contingency Theory's views of flexible crisis communication strategies to be received better by the publics.